Laser vs microdebrider eustachian tuboplasty for the treatment of chronic adult eustachian tube dysfunction: A systematic review - Waqas Jamil; Steve Izzat (World Journal of Otorhinolaryngology-Head and Neck Surgery, 2021)
Objectives: Multiple treatments are described in the literature for the treatment of chronic Eustachian tube dysfunction but high-level quality evidence seems missing to support these treatments. This systematic review aimed to determine and compare the safety and efficacy of Laser Eustachian tuboplasty and Microdebrider Eustachian tuboplasty as a treatment for long-term Eustachian tube dysfunction. Data sources: A total of 12 electronic databases were searched up to April 2018 for published and unpublished literature in the English language. References of included studies were checked. Methods: A systematic review was undertaken. Outcomes assessed were: primary outcomes-subjective improvement in symptoms (ETDQ-7), audiometric improvement of hearing, improvement of negative middle ear pressure noticed in tympanometry, objective improvement of tympanic membrane retraction. Secondary outcomes were-the ability to auto-insufflate Eustachian tube i.e. Valsalva manoeuvre, improved quality of life, passive tubal opening, tubomanometry, swallowing test, reduction in mucosal inflammation of Eustachian tube orifice in the nose, complications from the procedure, the need for further procedures. Results are reported in a narrative synthesis as a meta-analysis was not possible due to heterogeneous data. Results: Three studies were included. All included studies were small-scale case series (13–38 participants). Studies were conducted outside the UK. Subjective and objective improvement of Eustachian tube function was reported in all studies. But all included studies were at high risk of bias and subject to multiple limitations. No major complications were reported in either study. Conclusions: Based on current evidence, it is not possible to recommend the clinical use of either of these two interventions i.e. Laser or Microdebrider Eustachian tuboplasty. Lack of controlled studies was identified as a gap in the evidence. Future research should be directed toward designing randomised controlled trials. These trials should use strict standard methodology and reporting criteria. Future trials should make use of consensus statement document about Eustachian tube dysfunction definition, diagnostic methods, and outcome assessment criteria to design clinical trials.